Soft rock grouting material as well as preparation method and reinforcing method thereof

By using soft rock grouting materials prepared by using components such as industrial waste slag polymers, the problems of high cost and great environmental impact of soft rock reinforcement materials in the existing technology are solved, and efficient reinforcement and mechanical properties of soft rocks are achieved, which meets the requirements of green and environmental protection.

CN119822708APending Publication Date: 2025-04-15CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510089265.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Among the existing soft rock reinforcement technology, silicate cement-based materials have problems such as high production costs, potential damage to the environment, poor stability, and poor durability, which limits their application in soft rock grouting and filler curing.

Method used

Soft rock gravel materials are prepared by components such as industrial waste slag polymers, biological additives, water reducing agents and premature strength agents. Through the chemical reaction of industrial waste slag polymers and silicon oxides inside the soft rock, the gelled substances with three-dimensional three-dimensional network structure are generated to improve the compressive strength and permeability of the soft rock.

Benefits of technology

It achieves efficient reinforcement of soft rocks, improves unlimited compressive strength and permeability, reduces production costs, and conforms to the concept of green and environmental protection. It is suitable for soft rock slope management projects in a variety of complex geological environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822708A_ABST
    Figure CN119822708A_ABST
Patent Text Reader

Abstract

The invention discloses a soft rock grouting material and a preparation method and a reinforcement method thereof, the soft rock grouting material comprises the following components by mass: 12-18 parts of an industrial waste residue geopolymer, 2-6 parts of a biological additive, 1-3 parts of a water reducer, 0.5-1 part of an early strength agent, and 10-20 parts of deionized water; the industrial waste residue geopolymer is prepared from the following components in percentage by mass: 20 to 30 weight percent of zeolite powder, 50 to 60 weight percent of mineral powder, 10 to 15 weight percent of gypsum and 10 to 15 weight percent of alkali activator. According to the grouting material, the fluidity, the bleeding rate, the initial setting time and the final setting time are reduced, and the unconfined compressive strength of soft rock can be improved; according to the reinforcing method, the stability and mechanical property of the soft rock are improved by reducing the fracture rate and porosity of the soft rock and enhancing the interaction force among soft rock particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of engineering materials and relates to a soft rock grouting material and a preparation method and a reinforcement method thereof. Background Art

[0002] In the engineering field, loose, broken, weak and weathered expansive rocks with a strength range of 0.5 to 25 MPa are collectively referred to as soft rocks, which are easy to soften when exposed to water, have low shear strength and fragile particles. Soft rock slopes are widely distributed in Huguang and Guizhou in southern China. Because they contain a large amount of clay minerals, soft rock slopes are easily affected by the hot and humid climate in the region, resulting in collapse and cracking. This will lead to the degradation of its mechanical properties and impermeability, and may even cause natural disasters such as landslides and mudslides. With the continuous development of China's economy, a large amount of infrastructure construction is bound to be carried out in the distribution area of ​​soft rock. In order to ensure the safety of engineering construction in the region, it is necessary to find a method that can effectively reinforce soft rock and reduce the impact of climate and weather on the deterioration of soft rock.

[0003] In the field of geotechnical engineering, traditional soft rock reinforcement technology mainly uses silicate cement-based materials as grouting and curing materials. This material is widely adopted due to its excellent stability and high strength characteristics. However, its high production cost and significant impact on global climate change have caused concerns about potential damage to the ecological environment. At the same time, silicate cement-based materials have shortcomings such as poor stability, poor durability, and easy shrinkage cracks, which lead to large deformation and even collapse of soft rock slopes, resulting in huge economic losses. At present, modifiers for grouting and reinforcement materials have problems such as high cost, slow reaction rate, insignificant modification effect, and limited scope of application, which to a certain extent limit their application in the field of soft rock grouting and filler curing. Therefore, it is extremely important to develop a grouting and curing material suitable for soft rock, with efficient repair characteristics and green environmental protection. This ensures that the invented material can effectively guarantee the safety of engineering construction in the area. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a soft rock grouting material, which reduces the fluidity, water separation rate, initial setting time and final setting time, and can improve the unconfined compressive strength of soft rock.

[0005] The second object of the present invention is to provide a method for preparing a soft rock grouting material.

[0006] The second object of the present invention is to provide a reinforcement method for soft rock grouting materials, which improves the stability and mechanical properties of soft rock by reducing the soft rock crack rate and porosity and enhancing the interaction force between soft rock particles.

[0007] The technical solution adopted by the present invention is a soft rock grouting material, which comprises the following components by weight: 12 to 18 parts of industrial waste slag geopolymer, 2 to 6 parts of biological additives, 1 to 3 parts of water reducing agent, 0.5 to 1 part of early strength agent, and 10 to 20 parts of deionized water;

[0008] The industrial waste slag geopolymer comprises the following components according to mass fraction: 20-30wt% of zeolite powder, 50-60wt% of mineral powder, 10-15wt% of gypsum, and 10-15% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; and the standard sieve mesh of the zeolite powder is 200 meshes.

[0009] The embodiment of the present invention utilizes the chemical reaction process of depolymerization, recombination, condensation and polycondensation of the aluminum silicate and alkaline solution contained in the industrial waste slag geopolymer with the silicon oxide inside the soft rock to prepare a three-dimensional network structure of the gel; biological additives are added to the grouting and curing materials to improve the distance between the soft rock particles, reduce the friction between the gelling material and the aggregate, and improve the fluidity and working performance of the slurry. This ratio is determined after comprehensive consideration of theoretical calculations and field test results, and is verified through actual engineering application cases. According to the different requirements of on-site grouting or curing construction, the ratio of the corresponding grouting or curing materials is optimized and adjusted to ensure that the addition amount of each component is reasonable and significantly improve the mechanical properties of the material.

[0010] Furthermore, the biological additive is guar gum.

[0011] Furthermore, the water reducer is a composition in which lignin sulfonate, cellulose ether and sodium gluconate are mixed in a mass ratio of (2.5-3.5): (0.2-0.28): (0.15-0.25). The polar hydrophilic groups contained in the water reducer composition can form a stable water film, which can be adsorbed on the surface of soft rock particles, thereby changing its interfacial activity. Depending on the amount of the water reducer composition added, the trend of improving fluidity or enhancing curing performance is also different.

[0012] Furthermore, the early strength agent is a composition of aluminum sulfate, calcium nitrate and diethanolamine in a mass ratio of (2-2.5): (2-2.5): (1-1.5). Aluminum sulfate and calcium nitrate react with soft rock to generate a calcium hydrate compound, which can accelerate the hydration reaction, thereby improving the early strength of the cementitious material.

[0013] A method for preparing a soft rock grouting material comprises the following steps:

[0014] S1. Weigh the following parts by mass: 12-18 parts of industrial waste geopolymer, 2-6 parts of biological additives, 1-3 parts of water reducer, 0.5-1 part of early strength agent, and 10-20 parts of deionized water;

[0015] S2, at 20-25° C., the industrial waste geopolymer, biological additives and 60%-80% by weight of deionized water weighed in step S1 are transferred into a first container, and stirred at 220-250 r / min to mix evenly to obtain a viscous slurry;

[0016] S3. Pour the slurry of step S2, the water reducing agent, the early strength agent and the balance deionized water of 20% to 40% into a second container at 20 to 25° C., stir at 600 to 620 r / min to mix evenly, and obtain the slurry.

[0017] Furthermore, in S2, the stirring time is 50-60 min, and the stirring temperature is maintained at 30-40°C.

[0018] Furthermore, in S3, the stirring time is 240-250 min, and the stirring temperature is maintained at 50-60°C.

[0019] A method for reinforcing soft rock grouting materials, characterized in that it comprises the following steps:

[0020] Step 1, mechanically stir the soft rock to be solidified and the grouting material in a mass ratio of 75:6-8, and stir them evenly;

[0021] Step 2, sealing the mixture prepared in step 1 with a plastic film for 12 to 14 hours; then, filling it into the target area for reinforcement and performing compaction operations, with a compaction degree of more than 96%, to complete the reinforcement of the soft rock.

[0022] Furthermore, in step 1, the stirring time is 1 to 1.2 hours, and the stirring speed is 240 to 250 r / min.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention makes the working performance and mechanical properties of the grouting material suitable for soft rock slopes through reasonable material component design, thereby achieving the effect of reinforcing the slope. When the material is a solidifying material, it reacts with the silicon oxide inside the soft rock to generate a gelling substance, which is partially bonded to the sample surface and partially filled in the pores, so that the soft rock particles are bonded to each other to form agglomerates, thereby improving the compressive strength and impermeability of the soft rock. When the material is a grouting material, it plays the role of filling cracks and cementing rock blocks in the process of repairing soft rocks. After solidification, the discontinuously loaded broken rock samples are cemented into complete rock samples, thereby improving the mechanical strength of the injected broken rock samples and generating sufficient anti-destruction ability. The grouting strength repair rate using the material of the present invention can reach 72.41% to 89.67%.

[0025] 2. The grouting material prepared by the present invention, whose raw material is industrial waste slag geopolymer, has the advantages of convenient material acquisition and low cost. In addition, the use of industrial waste slag geopolymer not only effectively reduces the production cost, but also realizes the resource utilization of waste, which is consistent with the concept of green environmental protection. The high alkali excitation characteristics of the geopolymer enable it to fully react with the active ingredients in the soft rock during the reaction process to produce a gelling substance with a three-dimensional network structure, forming a dense solidified structure, which effectively hinders the mobility of free water inside the soft rock, thereby further enhancing the reinforcement effect. The use of this material for soft rock reinforcement has a simple construction process, and the mechanical properties of the reinforced soft rock are significantly improved, with good long-term stability, and is suitable for soft rock slope management projects under a variety of complex geological environments.

[0026] 3. The grouting material prepared by the present invention can accurately adjust the material ratio according to the characteristics of different soft rock construction objects to adapt to the changing geological conditions and engineering requirements. Specifically, by accurately controlling the mixing ratio of industrial waste slag geopolymer and soft rock, and adding an appropriate amount of biological additives, the setting time and curing strength of the material can be optimized. For example, in situations where the project requires higher strength, the ratio of geopolymer can be appropriately increased. In addition, the material also has good water resistance and high temperature resistance, and can maintain stable performance in harsh environments. Through this flexible ratio adjustment, not only the scope of application of the material is enhanced, but also the reliability and economy of the soft rock reinforcement project are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is the scanning electron microscope morphology of soft rock without any solidifying material.

[0029] Figure 2 This is the scanning electron microscope morphology of the soft rock after being treated with the grouting material prepared in Example 1.

[0030] Figure 3 It is a performance change diagram of the grouting material obtained by different mass ratios of the water reducing agent components in the embodiment of the present invention.

[0031] Figure 4 This is a performance change diagram of the grouting material obtained by using different mass ratios of the components of the early strength agent in the embodiment of the present invention.

[0032] Figure 5This is a performance change diagram of carbonaceous mudstone at different dosages of the solidifying material in Example 18; wherein a is the change in conductivity, b is the change in permeability coefficient, c is the unconfined compressive strength, and d is the unconfined compressive strength at different temperatures.

[0033] Figure 6a The unconfined compressive strength changes of multiple fractured silty mudstone samples treated with the grouting material prepared in Example 2 of the present invention.

[0034] Figure 6b The unconfined compressive strength of fractured silty mudstone treated with the grouting materials prepared in Examples 1-6 of the present invention at different temperatures.

[0035] Figure 7 It is a schematic diagram of the solidified carbonaceous mudstone sample.

[0036] Figure 8 It is a schematic diagram of the grouting reinforcement specimen of fractured silty mudstone using grouting materials. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] A method for preparing a soft rock grouting material comprises the following steps:

[0040] S1. Weigh the following parts by mass: 18 parts of industrial waste slag geopolymer, 6 parts of biological additives, 3 parts of water reducing agent, 1 part of early strength agent, and 20 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0041] S2. At room temperature (25° C.), the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0042] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature (25°C), stir and mix evenly at 600r / min, while maintaining the stirring temperature at 60°C, and stir for 240min to obtain.

[0043] Example 2

[0044] A method for preparing a soft rock grouting material comprises the following steps:

[0045] S1. Weigh the following parts by mass: 15 parts of industrial waste slag geopolymer, 6 parts of biological additives, 2 parts of water reducing agent, 1 part of early strength agent, and 18 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0046] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0047] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 60° C., and stir for 240 minutes to obtain the product.

[0048] Example 3

[0049] A method for preparing a soft rock grouting material comprises the following steps:

[0050] S1. Weigh the following parts by mass: 14 parts of industrial waste slag geopolymer, 3 parts of biological additives, 1 part of water reducing agent, 1 part of early strength agent, and 20 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0051] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0052] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 60° C., and stir for 240 minutes to obtain the product.

[0053] Example 4

[0054] A method for preparing a soft rock grouting material comprises the following steps:

[0055] S1. Weigh the following parts by mass: 14 parts of industrial waste slag geopolymer, 3 parts of biological additives, 3 parts of water reducing agent, 1 part of early strength agent, and 18 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0056] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0057] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 60° C., and stir for 240 minutes to obtain the product.

[0058] Example 5

[0059] A method for preparing a soft rock grouting material comprises the following steps:

[0060] S1. Weigh the following parts by mass: 17 parts of industrial waste slag geopolymer, 2 parts of biological additives, 1 part of water reducing agent, 0.5 part of early strength agent, and 20 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0061] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0062] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 60° C., and stir for 240 minutes to obtain the product.

[0063] Example 6

[0064] A method for preparing a soft rock grouting material comprises the following steps:

[0065] S1. Weigh the following parts by mass: 13 parts of industrial waste slag geopolymer, 2 parts of biological additives, 3 parts of water reducing agent, 0.5 parts of early strength agent, and 20 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0066] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 250 r / min, while maintaining the stirring temperature at 40° C. for 60 minutes to obtain a viscous slurry;

[0067] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 60° C., and stir for 240 minutes to obtain the product.

[0068] Example 7

[0069] The mass ratio of the early strength agent is aluminum sulfate: calcium nitrate: diethanolamine = 2.5:2.5:1, and the rest is the same as Example 2.

[0070] Example 8

[0071] The mass ratio of the early strength agent is aluminum sulfate: calcium nitrate: diethanolamine = 2:2:1.5, and the rest is the same as Example 2.

[0072] Example 9

[0073] The mass ratio of the water reducing agent is lignin sulfonate: cellulose ether: sodium gluconate = 3.5: 0.28: 0.15, and the rest is the same as in Example 2.

[0074] Example 10

[0075] The mass ratio of the water reducing agent is lignin sulfonate: cellulose ether: sodium gluconate = 2.5:0.2:0.25, and the rest is the same as in Example 2.

[0076] Comparative Example 1

[0077] No early strength agent was added, and the rest was the same as in Example 2.

[0078] Comparative Example 2

[0079] No water reducing agent was added, and the rest was the same as in Example 2.

[0080] Comparative Example 3

[0081] No early strength agent and water reducing agent were added, and the rest was the same as in Example 2.

[0082] Comparative Example 4

[0083] No biological additives were added, and the rest was the same as in Example 2.

[0084] The grouting materials of Examples 1 to 10 and Comparative Examples 1 to 4 were subjected to mechanical property tests and working performance tests. The test results are shown in Table 1.

[0085] Table 1 Grouting material performance test results

[0086]

[0087] The data in Table 1 show that the fluidity of Example 2 is 195 mm, the water separation rate is 1.9%, the initial setting time is 6 h, the final setting time is 9.5 h, and the 28-day unconfined compressive strength is 5.8 MPa. Compared with Comparative Example 1 without adding an early strength agent, the fluidity of Example 2 is reduced by 42.05%, the water separation rate is reduced by 163.16%, the initial setting and final setting times are reduced by 35% and 38.95% respectively, and the 28-day unconfined compressive strength is increased by 62.5%. Compared with Comparative Example 2 without adding a water reducing agent, the fluidity of Example 2 is reduced by 8.21%, the water separation rate is reduced by 63.16%, the initial setting and final setting times are increased by 25% and 35.79% respectively, and the 28-day unconfined compressive strength is increased by 55.17%. Compared with the comparative example 3 without adding the early strength agent and the water reducing agent, the fluidity of the embodiment 2 is reduced by 45.13%, the water separation rate is reduced by 184.21%, the initial setting and final setting time are increased by 50% and 38.95% respectively, and the 28d unconfined compressive strength is increased by 63.79%.

[0088] Embodiment 11

[0089] A method for preparing a soft rock grouting material comprises the following steps:

[0090] S1. Weigh the following parts by mass: 15 parts of industrial waste slag geopolymer, 4 parts of biological additives, 2 parts of water reducing agent, 0.75 parts of early strength agent, and 15 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0091] S2. At room temperature (20-25° C.), the industrial waste geopolymer, biological additive and 70% deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 240 r / min, while maintaining the stirring temperature at 35° C. for 55 minutes to obtain a viscous slurry;

[0092] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 30% of the remaining deionized water into a second container at room temperature, stir and mix evenly at 610 r / min, while maintaining the stirring temperature at 55° C., and stir for 245 minutes to obtain.

[0093] A method for reinforcing soft rock grouting materials, comprising the following steps:

[0094] Step 1, mechanically stir the soft rock to be solidified (carbonaceous mudstone) and the grouting material prepared by S3 at a mass ratio of 75:7, stirring for 1 hour, stirring at a speed of 245 r / min, and stirring evenly; the grouting material here is used as the solidification material;

[0095] Step 2: Use plastic film to seal the mixture prepared in step 1 for 13 hours. Then, fill the mixture into the target area for reinforcement and perform compaction operation, with a compaction degree of more than 96% to complete the reinforcement process of soft rock.

[0096] Example 12

[0097] A method for preparing a soft rock grouting material comprises the following steps:

[0098] S1. Weigh the following parts by mass: 12 parts of industrial waste slag geopolymer, 2 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 10 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0099] S2. At room temperature, the industrial waste geopolymer, biological additive and 60% deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 220 r / min, while maintaining the stirring temperature at 30° C. for 60 minutes to obtain a viscous slurry;

[0100] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 40% of the remaining ion water into a second container at room temperature, stir and mix them evenly at 600 r / min, while maintaining the stirring temperature at 50° C., and stir for 240 minutes to obtain the product.

[0101] A method for reinforcing soft rock grouting materials, comprising the following steps:

[0102] Step 1, mechanically stir the soft rock (carbonaceous mudstone) and the grouting material prepared from S3 at a mass ratio of 75:6, with a stirring time of 1.1 h and a stirring speed of 240 r / min, and stir evenly; the grouting material here is used as a solidifying material;

[0103] Step 2: Use plastic film to seal the mixture prepared in step 1 for 12 hours. Then, fill the mixture into the target area for reinforcement and perform compaction operation, with a compaction degree of more than 96% to complete the reinforcement process of soft rock.

[0104] Embodiment 13

[0105] A method for preparing a soft rock grouting material comprises the following steps:

[0106] S1. Weigh the following parts by mass: 18 parts of industrial waste slag geopolymer, 6 parts of biological additives, 3 parts of water reducing agent, 1 part of early strength agent, and 20 parts of deionized water; wherein the industrial waste slag geopolymer includes the following components by mass fraction: 20wt% of zeolite powder, 60wt% of mineral powder, 10wt% of gypsum, and 10% of alkali activator; the mineral powder is S95 grade granulated blast furnace slag; the standard sieve of zeolite powder is 200 mesh; the biological additive is guar gum; the water reducing agent is a composition of lignin sulfonate, cellulose ether, and sodium gluconate in a mass ratio of 3:0.24:0.2; the early strength agent is a composition of aluminum sulfate, calcium nitrate, and diethanolamine in a mass ratio of 2.25:2.25:1.25;

[0107] S2. At room temperature, the industrial waste geopolymer, biological additive and 80% of deionized water weighed in step S1 are transferred into a first container, and stirred and mixed evenly at 220 r / min, while maintaining the stirring temperature at 40° C. for 50 minutes to obtain a viscous slurry;

[0108] S3. Pour the slurry of step S2, water reducing agent, early strength agent and 20% of the remaining ion water into a second container at room temperature, stir and mix evenly at 620 r / min, while maintaining the stirring temperature at 60° C., and stir for 250 min to obtain the product.

[0109] A method for reinforcing soft rock grouting materials, comprising the following steps:

[0110] Step 1, mechanically stir the soft rock (carbonaceous mudstone) and the grouting material prepared from S3 at a mass ratio of 75:8, stirring for 1.2 hours, stirring at a speed of 250 r / min, and stirring evenly; the grouting material here is used as a solidifying material;

[0111] Step 2: Use plastic film to seal the mixture prepared in step 1 for 14 hours. Then, fill the mixture into the target area for reinforcement and perform compaction operation, with a compaction degree of more than 96% to complete the reinforcement process of soft rock.

[0112] Embodiment 14

[0113] S1. Weigh according to the following mass fractions:

[0114] 17 parts of industrial waste geopolymer, 3 parts of biological additives, 2 parts of water reducing agent, 0.5 parts of early strength agent, 12 parts of deionized water; the rest are the same as in Example 11;

[0115] Embodiment 15

[0116] S1. Weigh according to the following mass fractions:

[0117] 16 parts of industrial waste geopolymer, 4 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 17 parts of deionized water; the rest are the same as in Example 11.

[0118] Example 16

[0119] S1. Weigh according to the following mass fractions:

[0120] 16 parts of industrial waste geopolymer, 5 parts of biological additives, 2 parts of water reducing agent, 1 part of early strength agent, and 16 parts of deionized water; the rest are the same as Example 11.

[0121] Embodiment 17

[0122] S1. Weigh according to the following mass fractions:

[0123] 15 parts of industrial waste geopolymer, 6 parts of biological additives, 2 parts of water reducing agent, 1 part of early strength agent, and 18 parts of deionized water; the rest are the same as Example 11.

[0124] Embodiment 18

[0125] S1. Weigh according to the following mass fractions:

[0126] 14 parts of industrial waste geopolymer, 3 parts of biological additives, 1 part of water reducing agent, 1 part of early strength agent, and 20 parts of deionized water; the rest are the same as Example 11.

[0127] Embodiment 19

[0128] S1. Weigh according to the following mass fractions:

[0129] 14 parts of industrial waste geopolymer, 3 parts of biological additives, 3 parts of water reducing agent, 1 part of early strength agent, and 18 parts of deionized water; the rest are the same as Example 11.

[0130] Embodiment 20

[0131] S1. Weigh according to the following mass fractions:

[0132] 17 parts of industrial waste geopolymer, 2 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 20 parts of deionized water; the rest are the same as in Example 11.

[0133] Embodiment 21

[0134] S1. Weigh according to the following mass fractions:

[0135] 17 parts of industrial waste geopolymer, 3 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 18 parts of deionized water; the rest are the same as in Example 11.

[0136] Embodiment 22

[0137] S1. Weigh according to the following mass fractions:

[0138] 13 parts of industrial waste geopolymer, 2 parts of biological additives, 3 parts of water reducing agent, 0.5 parts of early strength agent, and 20 parts of deionized water; the rest are the same as in Example 11.

[0139] Embodiment 23

[0140] S1. Weigh according to the following mass fractions:

[0141] 13 parts of industrial waste geopolymer, 2 parts of biological additives, 2 parts of water reducing agent, 0.5 parts of early strength agent, and 10 parts of deionized water; the rest are the same as Example 11.

[0142] Embodiment 24

[0143] S1. Weigh according to the following mass fractions:

[0144] 14 parts of industrial waste geopolymer, 4 parts of biological additives, 1 part of water reducing agent, 1 part of early strength agent, and 12 parts of deionized water; the rest are the same as Example 11.

[0145] Embodiment 25

[0146] S1. Weigh according to the following mass fractions:

[0147] 15 parts of industrial waste geopolymer, 2 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 14 parts of deionized water; the rest are the same as in Example 11.

[0148] Embodiment 26

[0149] S1. Weigh according to the following mass fractions:

[0150] 18 parts of industrial waste geopolymer, 5 parts of biological additives, 1 part of water reducing agent, 0.5 parts of early strength agent, and 13 parts of deionized water; the rest are the same as in Example 11.

[0151] Embodiment 27

[0152] S1. Weigh according to the following mass fractions:

[0153] 18 parts of industrial waste geopolymer, 3 parts of biological additives, 3 parts of water reducing agent, 0.75 parts of early strength agent, and 10 parts of deionized water; the rest are the same as in Example 11.

[0154] Embodiment 28

[0155] S1. Weigh according to the following mass fractions:

[0156] 12 parts of industrial waste geopolymer, 2 parts of biological additives, 2 parts of water reducing agent, 1 part of early strength agent, and 11 parts of deionized water; the rest are the same as Example 11.

[0157] Embodiment 29

[0158] S1. Weigh according to the following mass fractions:

[0159] 18 parts of industrial waste geopolymer, 2 parts of biological additives, 2 parts of water reducing agent, 1 part of early strength agent, and 15 parts of deionized water; the rest are the same as Example 11.

[0160] Embodiment 30

[0161] S1. Weigh according to the following mass fractions:

[0162] 15 parts of industrial waste geopolymer, 4 parts of biological additives, 1 part of water reducing agent, 1 part of early strength agent, and 13 parts of deionized water; the rest are the same as Example 11.

[0163] Embodiment 31

[0164] The mass ratio of the early strength agent is aluminum sulfate: calcium nitrate: diethanolamine = 2.5:2.5:1, and the rest is the same as Example 17.

[0165] Embodiment 32

[0166] The mass ratio of the early strength agent is aluminum sulfate: calcium nitrate: diethanolamine = 2:2:1.5, and the rest is the same as Example 17.

[0167] Embodiment 33

[0168] The mass ratio of the water reducer is lignin sulfonate: cellulose ether: sodium gluconate = 3.5:0.28:0.15, and the rest is the same as Example 17.

[0169] Embodiment 34

[0170] The mass ratio of the water reducer is lignin sulfonate: cellulose ether: sodium gluconate = 2.5:0.2:0.25, and the rest is the same as Example 17.

[0171] Comparative Example 5

[0172] No solidifying material is used to solidify soft rock.

[0173] Comparative Example 6

[0174] S1. No early strength agent is added, and the rest is the same as Example 17.

[0175] Comparative Example 7

[0176] S1. No water reducing agent is added, and the rest is the same as Example 17.

[0177] Comparative Example 8

[0178] S1. No early strength agent and water reducing agent are added, and the rest is the same as Example 17.

[0179] Comparative Example 9

[0180] S1. No biological additives are added, and the rest is the same as Example 17.

[0181] Comparative Example 10

[0182] Cement, water-cement ratio 0.6; the effect is not as good as the embodiment of the present invention and is not green and environmentally friendly.

[0183] In the embodiment of the present invention, the grouting of soft rock refers to the grouting reinforcement of silty mudstone; and the filler solidification of soft rock refers to the solidification of carbonaceous mudstone.

[0184] The mechanical property test and permeability test were performed on the reinforced carbonaceous mudstone of Examples 11 to 34 and Comparative Examples 5 to 10. The test results are shown in Table 2.

[0185] Table 2 Performance test results of grouting materials for reinforcing carbonaceous mudstone

[0186]

[0187] The data in Table 2, such as the unconfined compressive strength of Example 23 is 2017 KPa, and the permeability coefficient is 2.16×10 -7 cm / s, compared with the comparative example 5 without adding solidifying material, the unconfined compressive strength is increased by 236%, and the permeability coefficient is reduced by 231%; it can be seen that after the grouting material of the embodiment of the present invention is added and solidified, the mechanical properties of the carbonaceous mudstone are significantly improved, and the permeability coefficient is greatly reduced.

[0188] From the data in Table 2, it can be found that using the grouting material of the embodiment of the present invention to reinforce carbonaceous mudstone can effectively improve the unconfined compressive strength and impermeability of soft rock. Figure 1 As shown in Table 2, the microstructure of the soft rock filler that has not been reinforced by the grouting material of the present invention shows more cracks and pores, and the structure is relatively loose. In addition, the unconfined compressive strength and impermeability of Example 5 in Table 2 are both poor. Figure 2 It can be known that the microstructure of the soft rock filler after being reinforced with the grouting material of the embodiment of the present invention is more compact and the pores are reduced. The grouting material reacts with the silicon oxide inside the soft rock to form a gelling substance, which is partially bonded to the surface of the sample and partially filled in the pores, so that the soft rock particles are bonded to each other to form agglomerates, thereby improving the compressive strength and impermeability of the soft rock. The higher the amount of industrial waste slag geopolymer, the better the mechanical properties and impermeability of the soft rock reinforcement; when the amount of biological additives is too much, a large amount of colloid precipitation similar to tofu dregs is likely to appear on the surface of the sample, which will lead to a weakening of the solidification effect on the soft rock cracks and softening of the internal structure of the soft rock, thereby limiting the increase in compressive strength. Figure 2The presented gelling substances are all products of the materials of the embodiments of the present invention, and can meet the requirements of grouting and reinforcement of various soft rocks.

[0189] The mass ratio of each component of the water reducing agent was changed, and the remaining steps were the same as in Example 2. The effects of different mass ratios of each component of the water reducing agent on the properties of the grouting material were as follows: Figure 3 shown by Figure 3 It can be seen that as the mass of lignin sulfonate, cellulose ether and sodium gluconate added increases, the unconfined compressive strength of the grouting material increases first and then decreases. The fluidity and water separation rate are positively correlated with the addition amount of lignin sulfonate, cellulose ether and sodium gluconate. The optimal mass ratio of water reducer is lignin sulfonate: cellulose ether: sodium gluconate = (2.5-3.5): (0.2-0.28): (0.15-0.25). The geopolymer reaction requires a strong alkaline environment, and the acidity will destroy the cellulose ether molecular chain and affect its rheological properties. Sodium gluconate can stabilize the pH value of the system, maintain the properties of cellulose ether and lignin sulfonate, and ensure good rheological properties. In addition, during the geopolymer reaction process, the role of lignin sulfonate is to charge the geopolymer particles, while the long-chain molecules of cellulose ether build space barriers around the particles. Sodium gluconate prevents metal ions from destroying the dispersion system, thereby achieving a better dispersion effect, more effectively promoting the completion of the geopolymer reaction, and finally obtaining a gelled substance. The combination of lignin sulfonate, cellulose ether and sodium gluconate shows a significant synergistic effect. In practical applications, the optimal mass ratio of these three materials can be used to customize the most suitable grouting material for soft rocks of different types and properties, thereby achieving the best grouting and curing effects.

[0190] The mass ratio of each component of the early strength agent was changed, and the remaining steps were the same as in Example 2. The effects of different mass ratios of each component of the early strength agent on the properties of the grouting material were as follows: Figure 4 shown by Figure 4It can be seen that as the amount of aluminum sulfate, calcium nitrate and diethanolamine added increases, the unconfined compressive strength of the grouting material tends to decrease. The fluidity and water separation rate are negatively correlated with the amount of aluminum sulfate, calcium nitrate and diethanolamine added. The optimal mass ratio of the early strength agent is aluminum sulfate: calcium nitrate: diethanolamine = (2-2.5): (2-2.5): (1-1.5). The ionic strength and composition of the geopolymer reaction system will change due to the addition of aluminum sulfate and calcium nitrate, which will in turn affect the reaction rate. The aluminum ions in aluminum sulfate and the calcium ions in calcium nitrate can participate in the reaction or act as catalysts to promote the dissolution and polymerization of aluminosilicates and reduce the setting time of the geopolymer. The mechanical properties and working performance of the geopolymer deteriorate. The complexation of diethanolamine on metal ions will hinder the normal reaction of some ions, which helps to slow down the setting time of the geopolymer reaction. The appropriate amount of early strength agent can significantly improve the early strength of the grouting material. However, excessive use not only fails to achieve the expected strengthening effect, but also leads to short setting time, incomplete reaction and other undesirable phenomena. Therefore, when using the three early strength agents in combination, their mass ratio must be strictly controlled to ensure that they can play the best synergistic effect.

[0191] Figure 5 The graph shows the performance changes of carbonaceous mudstone at different dosages of the grouting material in Example 18. Figure 5 (a) shows that the conductivity shows a downward trend as the amount of solidifying material (i.e., the mass ratio of solidifying material to carbonaceous mudstone in step 1) increases. This phenomenon reveals the gradual consumption of ionic components in the solidifying material during the reaction process, further confirming the progress of the solidification reaction. As the proportion of solidifying material increases, the overall conductivity of the soft rock decreases, which reflects the increase in the density of its internal structure. At the same time, the decrease in conductivity also reveals the reduction of internal pores in the material, thereby enhancing the anti-permeability of the soft rock. Figure 5 (b) shows that the permeability coefficient decreases with the increase of the amount of solidifying material. The cementitious substances generated by the solidifying material and the carbonaceous mudstone can effectively block the internal water flow path, thereby significantly improving the anti-permeability of the carbonaceous mudstone. In addition, the filling effect of the cementitious substances not only reduces the porosity inside the carbonaceous mudstone, but also improves its structural stability, further enhancing the overall mechanical properties of the carbonaceous mudstone. The durability and stability of the carbonaceous mudstone have been significantly improved, providing a reliable guarantee for engineering applications. Figure 5 (c) reveals that with the increase of the amount of solidifying material, the mechanical strength of the carbonaceous mudstone reinforcement body is significantly improved. This phenomenon can be attributed to the chemical reaction between the solidifying material and the carbonaceous mudstone particles, which affects the improvement of mechanical strength to a certain extent. The gelling material generated by the reaction fills the pores of the carbonaceous mudstone, enhances the bonding force between the particles, and enhances the overall mechanical properties. Figure 5(d) shows the unconfined compressive strength law of carbonaceous mudstone reinforcement at different temperatures. As can be seen from the figure, as the temperature increases, the compressive strength decreases. This is mainly because the high temperature environment will accelerate the chemical reaction rate between the solidified material and the carbonaceous mudstone, and the generated cementitious material structure is relatively loose, and the bonding force is weakened. In addition, high temperature may also cause the evaporation of water inside the material, further reducing its mechanical properties.

[0192] Figure 6a The strength ratio of different samples of the grouting material in Example 2 was used for fractured soft rock (fractured silty mudstone). Six soft rock samples were used to conduct a grouting repair effect test. Figure 6a It can be seen that the grouting strength repair rate using the material of the embodiment of the present invention can reach 72.41% to 89.67%. Although the grouting body has limited anti-destruction ability, its compressive performance is enhanced compared with the broken rock without grouting repair, and the broken integrity is increased. Figure 6b The unconfined compressive strength diagram of the grouting material for treating fractured silty mudstone at different temperatures was obtained for Examples 1-6. It can be seen from the figure that as the temperature increases, the compressive strength of each example decreases, and the largest decrease is in Example 2, which decreases by 75.86%. This phenomenon shows that high temperature environment has a significant adverse effect on the mechanical properties of grouting materials, especially under extreme temperature conditions, the compressive strength of the material will drop sharply.

[0193] Figure 7 is a schematic diagram of carbonaceous mudstone before and after reinforcement (Example 18), Figure 7 It can be seen that the structure of the reinforced carbonaceous mudstone has shown significant improvement. After grouting, the originally loose and fissured rock mass has effectively filled the fissures and significantly increased the overall density. The comparison in the figure clearly shows the difference before and after reinforcement. The surface of the reinforced rock mass is smoother and the internal structure is tighter. This change not only improves the mechanical properties of the rock mass, but also significantly enhances its anti-permeability, thereby extending the service life of the engineering structure.

[0194] Figure 8 The actual application effect of grouting materials in fractured silty mudstone is demonstrated. Specifically, Figure 8 The left picture shows the state of the fractured silty mudstone sample that has not been treated with grouting materials. The broken rock sample that has not been treated with grouting is filled layer by layer in the grouting mold, and roughly restores the original uncompacted shape. However, because the broken rock sample is no longer a complete rock sample, the broken rock blocks have not been stressed for a long time, and the rock block particles are difficult to cement, and it is difficult to shape without external support. Figure 8The right figure shows the state of the fractured silty mudstone sample after being treated with the grouting material in Example 1. The material of the present invention plays the role of filling cracks and cementing rock blocks in the process of repairing soft rocks. After solidification, the discontinuously loaded broken rock samples are cemented into complete rock samples, thereby improving the mechanical strength of the injected broken rock samples and generating sufficient anti-destruction ability.

[0195] The guar gum, water reducing agent and early strength agent in the embodiment of the present invention each have an effect on the geopolymer. The water reducing agent and early strength agent are mixed with three different materials, and the geopolymer has been added without the early strength agent and the water reducing agent. The grouting material in the embodiment of the present invention is not only a single geopolymer material, and all the materials participating in the reaction have a synergistic effect. The water reducing agent and the early strength agent in the embodiment of the present invention have the effect of adjusting the pH value of the geopolymer reaction, promoting the reaction of zeolite powder and slag, and reacting with the geopolymer to form a stable complex, enhancing the fluidity and curing effect of the material, and can still play a role in a high temperature environment.

[0196] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A soft rock grouting material, characterized in that: The components include the following by weight: 12-18 parts of industrial waste slag geopolymer, 2-6 parts of biological additives, 1-3 parts of water reducing agent, 0.5-1 parts of early strength agent, and 10-20 parts of deionized water; The industrial waste residue geopolymer comprises the following components according to mass fraction: 20-30wt% of zeolite powder, 50-60wt% of mineral powder, 10-15wt% of gypsum and 10-15% of alkali activator.

2. A soft rock grouting material according to claim 1, characterized in that: The biological additive is guar gum.

3. A soft rock grouting material according to claim 1, characterized in that: The water reducing agent is a composition in which lignin sulfonate, cellulose ether and sodium gluconate are mixed in a mass ratio of (2.5-3.5): (0.2-0.28): (0.15-0.25).

4. The soft rock grouting material according to claim 1, characterized in that: The early strength agent is a composition in which aluminum sulfate, calcium nitrate and diethanolamine are mixed in a mass ratio of (2-2.5): (2-2.5): (1-1.5).

5. A method for preparing a soft rock grouting material according to claim 1, characterized in that: The following steps are involved: S1. Weigh the following parts by mass: 12-18 parts of industrial waste geopolymer, 2-6 parts of biological additives, 1-3 parts of water reducer, 0.5-1 part of early strength agent, and 10-20 parts of deionized water; S2, at 20-25° C., the industrial waste geopolymer, biological additives and 60%-80% by weight of deionized water weighed in step S1 are transferred into a first container, and stirred at 220-250 r / min to mix evenly to obtain a viscous slurry; S3. Pour the slurry of step S2, the water reducing agent, the early strength agent and the balance deionized water of 20% to 40% into a second container at 20 to 25° C., stir at 600 to 620 r / min to mix evenly, and obtain the slurry.

6. The method for preparing a soft rock grouting material according to claim 5, characterized in that: In S2, the stirring time is 50 to 60 minutes, and the stirring temperature is maintained at 30 to 40°C.

7. The method for preparing a soft rock grouting material according to claim 5, characterized in that: In S3, the stirring time is 240-250 min, and the stirring temperature is maintained at 50-60°C.

8. A method for reinforcing soft rock grouting materials as claimed in claim 1, characterized in that: The following steps are involved: Step 1, mechanically stir the soft rock to be solidified and the grouting material in a mass ratio of 75:6-8, and stir them evenly; Step 2, sealing the mixture prepared in step 1 with a plastic film for 12 to 14 hours; then, filling it into the target area for reinforcement and performing compaction operations, with a compaction degree of more than 96%, to complete the reinforcement of the soft rock.

9. A method for reinforcing soft rock grouting materials according to claim 8, characterized in that: In step 1, the stirring time is 1 to 1.2 hours, and the stirring speed is 240 to 250 r / min.